Development of an ELISA to distinguish between foot-and-mouth disease virus infected and vaccinated animals utilising the viral non-structural protein 3ABC. Issue 4 (6th April 2022) - Zia, Muhammad Ashir; Dobson, Samuel J.; Rowlands, David J.; Stonehouse, Nicola J.; Shah, Muhammad Salahuddin; Habib, Mudasser
Abstract : Introduction. Foot-and-mouth disease (FMD) is a highly contagious and economically devastating viral disease of livestock and is endemic in much of Asia, including Pakistan. Vaccination is used to control disease outbreaks and sensitive diagnostic methods which can differentiate infected animals from vaccinated animals (DIVA) are essential for monitoring the effectiveness of disease control programmes. Tests based on the detection of the non-structural protein (NSP) 3ABC are reliable indicators of virus replication in infected and vaccinated populations. Hypothesis/Gap statement. Diagnosis of FMD is expensive using commercial ELISA kits, yet is essential for controlling this economically-important disease. Aim. The development of a low-cost diagnostic ELISA, using protein made in Escherichia coli . Methodology. In this study, the viral precursor protein 3ABC (r3ABC) was expressed in E. coli, solubilised using detergent and purified using nickel affinity chromatography. The fusion protein contained an attenuating mutation in the protease and a SUMO tag. It was characterised by immunoblotting and immunoprecipitation, which revealed antigenicity against virus-specific polyclonal sera. Using r3ABC, an indirect ELISA was developed and evaluated using field sera from healthy/naïve, vaccinated and infected animals. Results. The diagnostic sensitivity and specificity of the r3ABC in-house ELISA were 95.3 and 96.3% respectively. The ELISA was validated through comparison with the commercially available ID Screen FMD NSP competition kit. Results indicated good concordance rates on tested samples and high agreement between the two tests. Conclusion. The ELISA described here can effectively differentiate between infected and vaccinated animals and represents an important low cost tool for sero-surveillance and control of FMD in endemic settings.